Minor Modernisms: The Scottish Renaissance and the Translation of German-language Modernism. Issue 2 (May 2019) - Lyall, Scott
Abstract : Germany has been epitomised in the twentieth century as Britain's main rival and adversary. Yet Scottish modernists were influenced by Germany and German-language modernism to think more internationally about their nation and work, a cultural encounter that took place largely in and through translation. Willa and Edwin Muir, who in the early 1920s stayed at educational modernist A. S. Neill's experimental school in Germany, translated German-language modernists such as Kafka and Broch. Hugh MacDiarmid utilised translations of Nietzsche to inform his call for a renascent Scotland. Lewis Grassic Gibbon would write Sunset Song after reading Gustav Frenssen's regional novel Jörn Uhl . Behind this lies the contention that the breakup of world empires, such as the British and Austro-Hungarian, occasioned minor modernisms (to adapt Deleuze and Guattari) such as that in Scotland, and that translation was central to the emergence, impact, and transnationality of the Scottish renaissance movement.